2019
DOI: 10.1016/j.molcel.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A Non-canonical Role of YAP/TEAD Is Required for Activation of Estrogen-Regulated Enhancers in Breast Cancer

Abstract: Highlights d YAP/TEAD non-canonically bind to a group of ERa-bound enhancers d YAP/TEAD are required for estrogen-induced transcription and breast cancer growth d YAP/TEAD regulate enhancer activation by controlling the recruitment of MED1 d TEAD is recruited to ERa active enhancers through protein tethering trans-binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 60 publications
4
75
1
Order By: Relevance
“…AIB1 and the related p160 co-activators NCOA-1 and NCOA-2 interact with nuclear hormone receptors (e.g., estrogen and androgen receptors-ER and AR) that would, in turn, seem to be candidate Hippointeracting factors. Indeed, a recent paper [9] supports a model of YAP-ER crosstalk by a mechanism that resembles that proposed by Kushner et al (Fig 1B, left panel). This study found YAP-TEAD bind directly to ER and are required for estrogen-induced gene transcription and breast cancer growth.…”
supporting
confidence: 80%
“…AIB1 and the related p160 co-activators NCOA-1 and NCOA-2 interact with nuclear hormone receptors (e.g., estrogen and androgen receptors-ER and AR) that would, in turn, seem to be candidate Hippointeracting factors. Indeed, a recent paper [9] supports a model of YAP-ER crosstalk by a mechanism that resembles that proposed by Kushner et al (Fig 1B, left panel). This study found YAP-TEAD bind directly to ER and are required for estrogen-induced gene transcription and breast cancer growth.…”
supporting
confidence: 80%
“…45 The YAP-TEAD4 complex co-regulates ERĪ± for estrogen-regulated enhancer activation, indicating that a non-canonical TEAD4 mechanism is responsible for breast cancer growth. 10 On the other hand, activator protein-1 (AP-1, a dimer of JUN and FOS) is a transcription factor and proto-oncogene. 46 By ChIP-seq analysis, AP-1 was demonstrated to co-occupy chromatin with the TEAD-YAP/TAZ complex and to promote breast cancer cell proliferation.…”
Section: Cooperation With Transcription Factorsmentioning
confidence: 99%
“…TEAD4 is highly expressed in skeletal muscle, initial studies focused on its role in blastocyst formation 6 and reported that TEAD4 is required for specification of the trophectoderm lineage in preimplantation embryos. [6][7][8] Recently, TEAD4 was demonstrated to be a novel prognostic marker of gastric cancer, 9 breast cancer, 10 colorectal cancer, 11 melanoma, 12 laryngeal cancer, 13 and head-neck squamous cell carcinoma. 14 Apart from its role in the canonical Hippo-YAP/TAZ pathway, other studies have reported its participation in post-translational modifications, 9,15 crosstalk between cancer-related signaling pathways, 16 and cancer-causing mutations.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation that would be consistent with both of these observations might be that the Yki/Sd complex does not bind to the enhancer directly but rather via a protein-protein interaction with a different DNAbinding protein such as Mad. Indeed, it has recently been shown that in mammalian cells, a complex containing YAP1 and the Sd ortholog TEAD4 can bind to enhancers of ecdysoneregulated genes not by interacting with DNA sequences, but rather via another protein, estrogen receptor Ī±, that is already bound to the enhancer (Zhu et al, 2019). Recent studies also suggest a mechanism by which CtBP can function as a repressor of Sd-regulated genes.…”
Section: Regulation Of Ban By Ctbp Via the Hippo Pathwaymentioning
confidence: 99%